The role of work-family conflict and job role identification in moderated mediating the relationship between perceived supervisor support and employee proactive behaviors - Wang, Zhicheng (Frontiers in Psychology, 2022)
In recent years, the outbreak and persistence of COVID-19 has greatly changed the way people work, and encouraging employees to work online from home has become a new form of work for organizations responding to the epidemic. Based on the W-HR model, this paper explored supervisor support as a situational resource in the context of online office, aiming to verify the changes in work-family status caused by individuals facing the background of supervisor support, and then relate employees' proactive behavior. Meanwhile, the predicted moderating effect of job role identification on supervisor support and work-family conflict was verified by considering the role identification generated in the positive interaction between employees and supervisors as individual resources. In this study, 555 employees from enterprises in the provinces of Jiangsu and Guangdong were selected as the research participants, and data were recovered at two time nodes. The results show that: 1. Perceived supervisor support significantly relates employee proactive behavior.2. Work-family conflict mediates the relationship between perceived supervisor support and employee proactive behavior. 3. Job role identification has a significant moderating effect on the relationship between perceived supervisor support and work-family conflict, and high level of job role identification moderated the mediating effect of work-family conflict on perceived supervisor support and employee proactive behavior significantly. This paper expands the research perspective of employee proactive behavior. It can be used as a reference for enterprises to formulate strategies to improve employee proactive behavior in the process of digital reform.